Cost efficiency and resistance to chemical attack of a fly ash geopolymeric mortar versus epoxy resin and acrylic paint coatings - Tahri, W. (2017)
This article presents results of an experimental investigation on the resistance to chemical attack (with sulphuric, hydrochloric and nitric acid) of several materials: OPC concrete, high-performance concrete, epoxy resin, acrylic painting and a fly ash-based geopolymeric mortar). Three types of acids with three high concentrations (10, 20 and 30%) were used to simulate long-term degradation. A cost analysis was also performed. The results show that the epoxy resin has the best resistance to chemical attack independently of the acid type and the acid concentration. However, the cost analysis shows that the epoxy resin-based solution is the least cost-efficient solution being 70% above the cost efficiency of the fly ash-based geopolymeric mortar.